Single‐cell damage elicits regional, nematode‐restricting ethylene responses in roots. (6th May 2019) - Marhavý, Peter; Kurenda, Andrzej; Siddique, Shahid; Dénervaud Tendon, Valerie; Zhou, Feng; Holbein, Julia; Hasan, M Shamim; Grundler, Florian MW; Farmer, Edward E; Geldner, Niko
Abstract: Plants are exposed to cellular damage by mechanical stresses, herbivore feeding, or invading microbes. Primary wound responses are communicated to neighboring and distal tissues by mobile signals. In leaves, crushing of large cell populations activates a long‐distance signal, causing jasmonate production in distal organs. This is mediated by a cation channel‐mediated depolarization wave and is associated with cytosolic Ca 2+ transient currents. Here, we report that much more restricted, single‐cell wounding in roots by laser ablation elicits non‐systemic, regional surface potential changes, calcium waves, and reactive oxygen species (ROS) production. Surprisingly, laser ablation does not induce a robust jasmonate response, but regionally activates ethylene production and ethylene‐response markers. This ethylene activation depends on calcium channel activities distinct from those in leaves, as well as a specific set of NADPH oxidases. Intriguingly, nematode attack elicits very similar responses, including membrane depolarization and regional upregulation of ethylene markers. Moreover, ethylene signaling antagonizes nematode feeding, delaying initial syncytial‐phase establishment. Regional signals caused by single‐cell wounding thus appear to constitute a relevant root immune response against small invaders. Synopsis: Damage affecting large cell populations is communicated to neighboring and distal tissues by mobile signals in plants. This study reveals that single cell tissue damage in roots triggers a regional, non‐systemic ethylene response that can act as a defense mechanism against microscopic invaders such as nematodes. Single root‐cell wounding by laser ablation causes regional surface potential changes, calcium waves, and production of reactive oxygen species. Laser ablation in roots does not induce jasmonate responses, but regional ethylene production and signaling. Activation of ethylene signaling requires a distinct set of calcium channels and NADPH oxidases. Nematode attack elicits analogous responses to laser ablation. Ethylene signaling limits nematode feeding and delays initial syncytial phase establishment. Abstract : Tissue damage restricted to a limited root area triggers a non‐systemic ethylene response as a defense mechanism against microscopic invaders.